Analysis of Buffeting Response and Stay Cable Fatigue Damage in Super-Long-Span Carbon Fiber-Reinforced Polymer (CFRP) Cable-Stayed Bridges - Yuanqing Nie; Zhitian Zhang; Jiadong Zeng; Feiyu Han (Applied Sciences)
As the span of cable-stayed bridges continues to increase, traditional steel cables face challenges such as excessive self-weight, significant sag effects, and sensitivity to wind-induced vibrations. This study proposes two super-long-span cable-stayed bridge schemes with a main span length of 1500 m and identical girder cross-sections, employing steel cables and CFRP cables, respectively. Based on a discretized finite element model of stay cables, the global dynamic responses, cable vibration characteristics, and fatigue performance of both schemes were systematically evaluated using time-domain buffeting analysis and Miner’s linear fatigue damage accumulation theory. The results demonstrate that CFRP cables, benefiting from their lightweight and high-strength properties, significantly reduce the vertical, lateral, and torsional RMS responses of the main girder under the critical 3° angle of attack, achieving reductions of 31.6%, 28.5%, and 20.6% at mid-span, respectively. Additionally, CFRP cables suppress cable–girder internal resonance through frequency decoupling. Fatigue analysis reveals that the annual fatigue damage of CFRP cables under the design wind speed is far lower than that of steel cables and remains well below the critical threshold, highlighting their superior fatigue resistance. This research confirms that CFRP cables can effectively enhance the aerodynamic stability and long-term durability of super-long-span cable-stayed bridges, providing theoretical support for span breakthroughs. To further ensure long-term service safety, this study recommends implementing damping measures at critical cable locations.